Unlocking the potential of resistant starches from underutilized tropical fruits as substrates for fermentation into short-chain fatty acids - Kembabazi, Stellamaris; Mutambuka, Martin; Shukri, Radhiah; Anwar, Farooq; Zawawi, Norhasnida (Elsevier, 2025)
Resistant starches (RS) are non-digestible, low molecular weight polysaccharides that, when consumed, act as prebiotics and provide multiple physiological benefits. Colonic fermentation of RS can yield short-chain fatty acids (SCFAs), which have therapeutic potential against metabolic disorders such as diabetes, obesity, over weight, and hypertension. Underutilized fruits have shown remarkable potential as sources of RS that can be fermented into SCFAs. This review explores the possibility of various underutilized tropical fruits as sources of RS and their prospective uses in producing SCFAs. The factors influencing the yield of SCFAs and the pathways and mechanisms of colonic fermentation are also assessed. The physiological benefits of RS-derived SCFAs are also reviewed. Exploiting the under-utilized fruit starches in the production of SCFAs will add value to natural resources and offer various physiological benefits to protect consumers' health.